PENERAPAN LEVERS OF CONTROL DALAM MENINGKATKAN KINERJA PADA FAMILY BUSINESS PT X DI SURABAYA - Richard Han (Jurnal Riset Akuntansi dan Keuangan, 2022)
The right management control systems for every company can’t be equated, because there are variables that differentiate every company. Therefore, in this research we will conduct a research on how management control systems, by applying levers of control by Simons(1995) can increase employee performance and help a family-business, in overcoming their problems for sustainability of the company. The object of this research is a car rent company family-business, PT. G. This research used qualitative approach, applied, and explanatory research method. The source of data collection for this research are interview, observation, and data analysis. According to Simons(1995), implementation of Levers of Control have to be balance, but did not means equal weight of each control levers, each company need diverse combination of control levers that are compatible to their company conditions. In this research were given some recommendation for PT. G to increase their control systems so their employee performance can increase as well.